A Wearable Photobiomodulation Patch Using a Flexible Red‐Wavelength OLED and Its In Vitro Differential Cell Proliferation Effects. Issue 5 (8th March 2018) - Jeon, Yongmin; Choi, Hye‐Ryung; Lim, Myungsub; Choi, Seungyeop; Kim, Hyuncheol; Kwon, Jeong Hyun; Park, Kyoung‐Chan; Choi, Kyung Cheol
Abstract: Photobiomodulation (PBM) is a safe and noninvasive method that can provide various clinical effects. However, conventional PBM devices using point light sources, such as light‐emitting diodes and lasers have various disadvantages, such as low flexibility, relatively heavy weight, and nonuniform effects. This paper presents a novel wearable PBM patch using a flexible red‐wavelength organic light‐emitting diode (OLED) surface light source, which can be attached to the human body as a personalized PBM platform. The palm‐sized wearable PBM patch can be very light (0.82 g) and thin (676 µm). It also has a reasonable operation life (>300 h), flexibility (20 mm bending radius), and low‐temperature operation (<40 °C), and it can provide wide and safe application irrespective of location and time. Fibroblasts, a major type of dermal cells, play a key role in the wound healing process. The results show that OLEDs may have excellent in vitro wound healing effects because they effectively stimulate fibroblast proliferation (over 58% of control) and enhance fibroblast migration (over 46% of control) under various conditions. For maximum effect, peak wavelength control is necessary to optimize cell proliferation and enhance in vivo wound healing effects. Abstract : Based on a flexible red‐wavelength OLED, a wearable photobiomodulation patch for wound healing is demonstrated. The patch excellently promotes in vitro wound healing. It also has a reasonable operation reliability, flexibility, and offers low‐temperature operation, so it can provide wide application irrespective of location and time attached to the human body.